Integrating Science and Scientific Information in Messages for Effective Communication during Pandemic and Beyond—Special Reference to COVID-19 Pandemic - Shimray, Chong (SCHOOL SCIENCE, 2020)
An enormous volume of information is being circulated since the beginning of the COVID-19 pandemic by all and sundry using all possible mediums, mostly electronic media, thanks to internet facilities which are now available at everybody’s disposal. Barring those official publications of the governments or organisations such as WHO, much of the information were not checked, verified, or authenticated by experts. As a result, misinformation and disinformation spread faster than the virus itself leading to pandemic-induced attitudes such as undue fear, over-complacency, utter carelessness, unnecessary bravado, vaccine-hesitancy, etc., among the public. The information circulated are often haphazard without considering the what, when, where, how, for whom, and who components. Most importantly, much of the information circulated even by authentic sources were mostly ‘instructions’ to make the public aware about the DOs and DON’Ts but lacked information on the science behind such instructions. Understanding the basic science behind it could help avoid some, if not all, pandemic-induced attitudes. Hence, there is a need for effective communication to fight pandemic which can be achieved only when the research community and professionals in different disciplines such as epidemiology, social sciences, research and development, diplomacy, logistics, and crisis management come together. Such efforts need to be made even beyond the COVID-19 pandemic.